Structural determinants for binding to angiotensin converting enzyme 2 (ACE2) and angiotensin receptors - Clayton, Daniel; Hanchapola, Iresha; Thomas, Walter G.; Widdop, Robert; Smith, Alexander I.; Perlmutter, Patrick; Aguilar, Marie-Isabel (Frontiers in Pharmacology, 2015)
Angiotensin converting enzyme 2 (ACE2) is a zinc carboxypeptidase involved in the renin–angiotensin system (RAS) and inactivates the potent vasopressive peptide angiotensin II (Ang II) by removing the C-terminal phenylalanine residue to yield Ang1–7. This conversion inactivates the vasoconstrictive action of Ang II and yields a peptide that acts as a vasodilatory molecule at the Mas receptor and potentially other receptors. Given the growing complexity of RAS and level of cross-talk between ligands and their corresponding enzymes and receptors, the design of molecules with selectivity for the major RAS binding partners to control cardiovascular tone is an on-going challenge. In previous studies we used single β-amino acid substitutions to modulate the structure of Ang II and its selectivity for ACE2, AT1R, and angiotensin type 2 (AT2R) receptor. We showed that modification at the C-terminus of Ang II generally resulted in more pronounced changes to secondary structure and ligand binding, and here, we further explore this region for the potential to modulate ligand specificity. In this study, (1) a library of 47 peptides derived from the C-terminal tetrapeptide sequence (-IHPF) of Ang II was synthesized and assessed for ACE2 binding, (2) the terminal group requirements for high affinity ACE2 binding were explored by and N- and C-terminal modification, (3) high affinity ACE2 binding chimeric AngII analogs were then synthesized and assessed, (4) the structure of the full-length Ang II analogs were assessed by circular dichroism, and (5) the Ang II analogs were assessed for AT1R/AT2R selectivity by cell-based assays. Studies on the C-terminus of Ang II demonstrated varied specificity at different residue positions for ACE2 binding and four Ang II chimeric peptides were identified as selective ligands for the AT2 receptor. Overall, these results provide insight into the residue and structural requirements for ACE2 binding and angiotensin receptor selectivity.